Investigation of a non-invasive venous blood flow measurement device: Using thermal mass measurement principles - Stewart, Kent; Dangelmaier, Simon; Pott, Peter; Anders, Jens (Current directions in biomedical engineering, 2019)
Venous blood circulation can be restricted due to various conditions commonly indicating a related medical condition. However, current non-invasive methods for determining venous blood flow are limited to be either very inaccurate or expensive. Alternatively, a method to measure sap flow non-invasively in trees is through thermal mass measurement principles. This paper investigates applying the thermal mass flow measurement principle to determine venous blood flow. A simplified finite element model (FEM) and simulation are created to determine the operating behavior and expected response of a thermal mass flow meter with venous blood flow under the skin. An initial prototype of a thermal mass venous blood flow meter is designed using a Peltier-element and RTD thermistors. Initial tests were done on N = 8 subjects identifying the presence of blood flow and, testing the devices basic functionality and performance. The simplified FEM model of venous blood flow proved the thermal mass blood flow device is feasible, and determined the initial characteristics of the first prototype. The initial prototype proved to be functional detecting rises in temperature downstream of +1.4 K (0.8 - 1.8 inter- quartile range) when the blood flow was released (t = 90 s after release), compared to when blood was not flowing. The initial prototype proved to be able to detect the presence of blood flow in all subjects. However, further work is required to increase the differences in temperature values or gradient measured for a change in flow rate so the actual flow rate can be determined.